A Preliminary Investigation into Technology and Processes Facilitating the Assurance of Learning - von Konsky, Brian; Watkins, Annette; Atkinson, Doug; Broadley, Tania (Massey University, 2012)
This paper reports on the outcomes from a preliminary evaluation of technologies and processesintended to support the Assurance of Learning initiative in the business faculty of an Australianuniversity. The study investigated how existing institutional information systems and operationalprocesses could be used to support direct measures of student learning and the attainment ofintended learning goals. The levels at which learning outcomes had been attained were extractedfrom the University Learning Management System (LMS), based on rubric data for threeassessments in two units. Spreadsheets were used to link rubric criteria to the learning goalsassociated with the assessments as identified in a previous curriculum mapping exercise, and toaggregate the outcomes. Recommendations arising from this preliminary study are made to informa more comprehensive pilot based on this approach, and manage the quality of student learningexperiences in the context of existing processes and reporting structures.